A phosphorylation-wide sncRNA screen reveals Protein Functional Effector sncRNAs (pfeRNAs) in human lung somatic cells. (28th June 2017) - Gable, Tyler; Wang, Yuyan; Clark, David; Kumari, Priti; Shetty, Amol Carl; Li, Mao; Mei, Yuping
Abstract: We recently reported that PIWI-interacting RNAs likes (piR-Ls) could regulate functions of the interacting phosphorylated proteins (p-Proteins). In addition, except for writers and erasers, functional efficacy of p-Proteins on their readers still remains unknown. We, therefore, reasoned there was a type of sncRNAs which could regulate functional efficacy of p-Proteins. Here, we profiled sncRNAs interacting with phosphorylated -Ser, -Thr and -Tyr residues in 3 HBE and 4 lung SCC cell lines, investigated effects and mechanisms of phosphorylated-residue-interacting sncRNAs. Our results demonstrated sncRNAs regulating functional efficacy of p-Proteins and we thus referred them as Protein Functional Effector sncRNAs (pfeRNAs). pfeRNAs were distributed among 26 to 50 nucleotides, shared some core sequences and showed distinctive expression patterns between HBE and SCC cells. Core sequences 417 (CS417), showing consistent upregulation in all 4 SCC cells, bound directly to p-Nucleolin (NCL), which was dependent on the key elements CGCG of CS417 and p-Ser619 of NCL. The CS417/p-NCL interaction was critical for functional efficacy of p-NCL in basic activities of lung normal and cancer cells. Thus, we revealed a novel type of pfeRNAs controlling functional efficacy of p-Proteins in lung somatic cells. Highlights: A phosphorylation-wide sncRNA screen in human lung somatic cells reveals pfeRNA. Functional assays validate the essentiality of formerly uncharacterized functional efficacy of p-Proteins. Phosphorylated residues of p-Proteins are indispensable for interaction with key elements of pfeRNAs. pfeRNA-induced abnormal efficacy of p-Proteins in lung squamous cell carcinoma.